Introduction to mathematical statistics - Hoel, Paul Gerhard (New York : Wiley, 1971)
The reorganization of material required considerable rewriting of the text. This was particularly true in the early chapters on probability in which it was necessary to formalize the notation and treatment. The later chapters differ very little from those of the earlier edition except the choice of topics.
Includes index.
osa 24/01/2019
Loans
Keywords: Mathematical statistics